An unusual isolated anterior mediastinal lesion. Issue 11 (19th October 2022) - Quigley, Nicholas; Lang‐Lazdunski, Loic; Boily‐Daoust, Catherine; Couture, Christian; Fortin, Marc
Abstract: Malignant pleural mesothelioma (MPM) is an infrequent tumour of poor prognosis with a strong association with asbestos exposure. Pleural effusion or thickening is the most common radiological finding. Thoracoscopic biopsy is the diagnostic modality of choice. In our report, we present the case of a career welder who consulted with vocal cord palsy and an atypical anterior mediastinal lesion. An EBUS‐TBNA‐guided biopsy and a thorough cytological assessment led to an unexpected diagnosis of epithelioid MPM. A localized anterior mediastinal lesion is an extremely infrequent presentation of MPM that deserves clinical recognition. Abstract : In our report, we present the case of a career welder who consulted with vocal cord palsy and an atypical anterior mediastinal lesion. An EBUS‐TBNA‐guided biopsy and a thorough cytological assessment led to an unexpected diagnosis of epithelioid malignant pleural mesothelioma (MPM). A localized anterior mediastinal lesion is an extremely infrequent presentation of MPM that deserves clinical recognition.